Building Community: Partnering with Students and Faculty to Design a Library Exhibition Space. Issue 3 (2nd April 2016) - Leousis, Kasia; Sproull, Robert
ABSTRACT: An academic library's space has traditionally operated as a repository, but with the proliferation of new media and interactive technologies, libraries now also serve as incubators of ideas. Architecture students at Auburn University recently took part in renovating the design library. With the librarian acting as client, they were asked to investigate diverse materials and design methods to create a dynamic and interactive exhibition wall which would showcase the creation of new knowledge and facilitate the dissemination of new information. This article discusses how the plug-in wall acted as a catalyst for the school's renewed communal investment in the library.